2018
DOI: 10.1016/j.ejmech.2018.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Hemozoin inhibiting 2-phenylbenzimidazoles active against malaria parasites

Abstract: The 2-phenylbenzimidazole scaffold has recently been discovered to inhibit β-hematin (synthetic hemozoin) formation by high throughput screening. Here, a library of 325,728 N-4-(1Hbenzo[d]imidazol-2-yl)aryl)benzamides was enumerated, and Bayesian statistics used to predict β-hematin and Plasmodium falciparum growth inhibition. Filtering predicted inactives and compounds with negligible aqueous solubility reduced the library to 35,124. Further narrowing to compounds with terminal aryl ring substituents only, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…It should be noted, however, that while the strongest interaction is predicted to be with the [001] face, this does not imply that no interaction occurs with other faces. Indeed, in a recent investigation of benzimidazole haemozoin inhibitors we found that docking to both the [001] and [011] faces needed to be considered to explain observed activity 21 . experimental tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that while the strongest interaction is predicted to be with the [001] face, this does not imply that no interaction occurs with other faces. Indeed, in a recent investigation of benzimidazole haemozoin inhibitors we found that docking to both the [001] and [011] faces needed to be considered to explain observed activity 21 . experimental tests.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that 103 of 155 compounds with this fingerprint were active in the β-haematin inhibition assay while 194 of 194 compounds were active in the parasite growth inhibition activity assay 31 . That study led to the synthesis of benzimidazole analogues, 83% of which were found to inhibit β-haematin formation and 50% inhibited parasite growth 21 . Although 9 showed one of the best β-haematin inhibitory activities, curiously, three out the five benzimidazole compounds identified in this series (compound 5, 7, and 14) were β-haematin and parasite inactive (with compound 14 weakly active against P. falciparum).…”
Section: Resultsmentioning
confidence: 99%
“…A molecular docking study conducted to attempt to rationalise these findings indicated that the lack of activity of the smaller fragments was probably a result of fewer contacts with the crystal surface, even though the benzimidazole fragment was the key pharmacophore. The most active benzimidazoles had a higher number of π-stacking interactions with the β-haematin crystal [21].…”
Section: In Vitro Assays Of the Usfda Approved Drugsmentioning
confidence: 99%
“…It should also be noted that while the strongest interaction is predicted to be with the [001] face, this does not necessarily imply that no interaction occurs with other faces. In a recent investigation of benzimidazole haemozoin inhibitors, we found that not only docking to the [001] face of β-haematin but also to the second fastest growing [011] face had to be considered to explain the observed activity [21]. The absence of these additional binding modes may play a role in reducing the accuracy of the model, as may the absence of solvents and lack of steps and kinks at the surface of the crystal, which are known to represent sites of drug binding [4].…”
Section: Structure-based Virtual Screening Against the β-Haematin Crymentioning
confidence: 99%
“…Following the application of Bayesian statistics and docking simulations, L′abbate et al. selected benzimidazole 51 for optimisation, culminating in a handful of compounds including 54 , whose excellent β‐hematin inhibitory activity translated into sub‐micromolar anti‐plasmodial activity …”
Section: Antimalarial Agentsmentioning
confidence: 99%